Formulation of Snail Slime (Achatina Fulica) Anti-Acne Emulgel using Tween 80-Span 80 as Emulsifying and HPMC as Gelling Agent - Nur Saadah Daud; Achnis Jum Akbar; Eny Nurhikma; Karmilah Karmilah (Borneo Journal of Pharmacy, 2018)
Acne is the condition of abnormal skin which is indicated by inflammation caused by the bacterial infection of Propionibacterium acnes. The natural one which can be used for the medical treatment of acne is the snail mucus (Achatina fulica). The achasin protein of it has antibacterial activity. That snail mucus was made to the emulgel form. This research has used an experimental method and the emulgel formulation used the various concentration of emulsifying agents and the gelling agent. They were Tween 80 1.76%, 2.44%, 3.12%, Span 80 2.24%, 4.06%, 5.88% and HPMC 3.5%, 4.5%, 5.5%. Other additives were propylene glycol, Methylparaben, Propylparaben, paraffin liquid, menthol, and aquadest. Those formulations were tested in physical evaluation during 4 weeks of storage in room temperature, irritation test, hedonic test, and cycling test. The organoleptic test showed that the emulgel were the milk-white color with a distinctive smell. All emulgel were homogenous, non-irritant, with emulsion type oil in water (o/w). This emulgel also met the normal skin of pH value and spread ability’s range. The emulgel viscosity shift was < 10%, with the viscosity value inversely proportional to spreadability. Formula C with 3.12% of Tween 80, 5.88% of Span 80 and 5.5% of HPMC was claimed as the most stable formula both in room temperature and after cycling test. It was also the most preferred by the panelist.